2018
DOI: 10.1111/iju.13830
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and outcomes in patients with unresectable or metastatic renal cell carcinoma in Japan

Abstract: Objectives To clarify treatment patterns and outcomes for patients with unresectable or metastatic renal cell carcinoma in the molecular target therapy era in Japan. Methods A multicenter, retrospective medical chart review study was carried out. Patients diagnosed with unresectable or metastatic renal cell carcinoma between January 2012 and August 2015 were enrolled. Data extracted from medical records included treatment duration, grade ≥3 adverse events, reason for discontinuation for each targeted therapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
(46 reference statements)
2
23
1
Order By: Relevance
“…A total of 20-40% of RCC patients have recurrent metastatic disease after a primary nephrectomy; therefore, approximately 50% of all patients who are diagnosed with RCC should receive systemic therapy during the course of their disease [2]. The prognosis of advanced and metastatic RCC is not satisfactory, even with the recent evolution of treatment methods [3]. RCC is classified into many subtypes, including clear cell RCC, which accounts for 70% of all RCC [4].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 20-40% of RCC patients have recurrent metastatic disease after a primary nephrectomy; therefore, approximately 50% of all patients who are diagnosed with RCC should receive systemic therapy during the course of their disease [2]. The prognosis of advanced and metastatic RCC is not satisfactory, even with the recent evolution of treatment methods [3]. RCC is classified into many subtypes, including clear cell RCC, which accounts for 70% of all RCC [4].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, molecular-targeted therapies have been generally used for treatment of mRCC. [1][2][3][4][5][6][7][8][9][10][11] As prognoses in mRCC have improved, more precise stratifications based on risk factors have been required. In the molecular-targeted therapy era, the IMDC risk classification is a standard riskbased stratification.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, molecular‐targeted therapies have been generally used for treatment of mRCC . As prognoses in mRCC have improved, more precise stratifications based on risk factors have been required.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, Harada et al clearly showed the real-world treatment pattern and outcome in the era of molecular-targeted therapy (MT-era) before the development of immuno-oncology (IO) agents. 3 In the MT-era, the distribution of used agents is likely to reflect the clinical situation. Pazopanib, which is recommended as a first-line treatment, was released 6 years after the release of sunitinib.…”
Section: Editorial Commentmentioning
confidence: 99%
“…In the present study, Harada et al . clearly showed the real‐world treatment pattern and outcome in the era of molecular‐targeted therapy (MT‐era) before the development of immuno‐oncology (IO) agents …”
mentioning
confidence: 99%